"Books I Used as a Child were Mathematically Incorrect": Reasons to Use Children's Shape-Related Books as a Resource to Improve Mathematical Knowledge for Teaching. Issue 3 (2021) - Nurnberger-Haag, Julie; Singh, Rashmi; , Jamie L. W. Wernet; Alexander, Anita N.
No abstract available